Overview of non-methane volatile organic compounds for world economy: From emission source to consumption sink - Jian Deng (Energy Nexus, 2022)
Non-methane volatile organic compounds are the primary culprit of regional ozone and photochemical pollution. To explore the relationship between non-methane volatile organic compounds and world economies, this study tracked the emission from production sources to final consumption sinks embodied in global supply chain in the framework of system input-output analysis model. The feedback from society to economic system is also covered. The emission embodied in global trade amounts to 58% of global total direct emission, .moreover, it is revealed that global NMVOCs transfer in intermediate trade is in magnitude more than double that in final trade. And around 34% global emission footprint feedback from society back to the economic system via primary inputs. Regional results reveal that the bulk of the world population, which is mainly in underdeveloped regions, has both a lower footprint per capita and footprint intensity compared with the global average level, respectively. Results show that regions including China and the United States have huge emission transfer imbalance in both intermediate trade and final trade. Considering the scale of emission imbalance, China, the United States and Europe are selected as representative cases for analysis. The reasons behind their imbalance are majorly attributed to two points: 1) Currency status; 2) Industrial transferring effect. Finally, this research suggests that economically developed regions should undertake more emission reduction responsibilities by furtherly investing in emission reduction technologies innovation, regulation policy promotion and public awareness-raising globally.